Family Roles in Parenting of International Migrant Workers - Nurhidayati, Tri; Rahayu, Desy Ariyana; Mubin, M Fatkul (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2016)
Abstract.This study aims to identify the role of the family in the care of migrant workers on the psychosocial development of children and families of children of migrant workers who left to work abroad. It is based on some research that families Become overburdened entrusted with the child, the child's relationship with the mother Becomes tenuous, Unruly children and school dropouts. This study was a descriptive study, analyze and describe the role of the international family of migrant workers in childcare. Analysis used univariate analysis. Research results Obtained good family role as many as 22 people (55%) and not well 18 people (45%). item No. 10 Observe the activities of children outside school activities doubt answer, sometimes and never showed more than 50%. Families are advised to payattention to the children's learning process and socialization of children.